Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Exotic Invasive Plant Species Increase Primary Productivity, but Not in Their Native Ranges - Ragan M. Callaway; Robert W. Pal; Adrian Schaar; David Hooper; Harald Auge; Isabell Hensen; Kevin Kožić; Ylva Lekberg; Dávid U. Nagy; Julian A. Selke; Arpad E. Thoma; Sabrina Träger; et al. (Ecology Letters, 2025)
Ecosystem net primary productivity is thought to occur near the maximum that abiotic constraints allow; but exotic invasive plants often correlate with increased productivity. However, field patterns and experimental evidence for this come only from the non‐native ranges of exotic species. Thus, we do not know if this pattern is caused by exotic invasions per se or whether successful exotic species are disproportionately productive or colonise more productive microsites. We measured aboveground biomass in the field and in common gardens with five plant species in their native and non‐native ranges. For all species combined, exotic invaders increased total plot productivity in their non‐native ranges by 91% in the field, and by 107% in the common garden, but had much smaller or no such effects in their native ranges. Thus, exotic invaders appear to be a driver of increased productivity, not simply a passenger, but only in their non‐native ranges.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Diseases of the giant river prawn Macrobrachium rosenbergii : A review for a growing industry - Chantelle Hooper; Partho P. Debnath; Grant D. Stentiford; Kelly S. Bateman; Krishna R. Salin; David Bass (Reviews in Aquaculture, 2023)
The giant river prawn, Macrobrachium rosenbergii , is a major focus of aquaculture in tropical and sub‐tropical regions around the globe. Over the last 30 years, culture of M . rosenbergii has increased exponentially as demand has risen both for domestic consumption and for international export trade. As with many aquaculture species increases in production have been accompanied by the emergence of diseases affecting yield, profit and trading potential. Disease‐causing agents include pathogens infecting other crustaceans, such as Decapod Iridescent Virus (DIV1), as well as pathogens only known from M . rosenbergii such as White Tail Disease caused by Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV). Here, we review the pathogenic agents associated with the culture of M . rosenbergii since commercial culture began in earnest during the 1970s. Particular emphasis is given to pathogens first identified in other aquaculture host species, but which have subsequently been shown to infect and cause disease in M . rosenbergii . As polyculture of M . rosenbergii with other aquaculture species is common practice, including culture with other decapods, crabs and fish, increased pathogen transfer among these farmed species may occur as M . rosenbergii aquaculture increases in the future.

PIM3 kinase promotes tumor metastasis in hepatoblastoma by upregulating cell surface expression of chemokine receptor cxcr4 - Raoud Marayati; Janet Julson; Laura V. Bownes; Colin H. Quinn; Laura L. Stafman; Andee M. Beierle; Hooper R. Markert; Sara C. Hutchins; Jerry E. Stewart; David K. Crossman; Anita B. Hjelmeland; Elizabeth Mroczek-Musulman; et al. (Clinical & Experimental Metastasis, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Identification of Semiochemicals from Cowpea, Vigna unguiculata, for Low-input Management of the Legume Pod Borer, Maruca vitrata - Jonathan Osei-Owusu; József Vuts; John C. Caulfield; Christine M. Woodcock; David M. Withall; Antony M. Hooper; Samuel Osafo-Acquaah; Michael A. Birkett (Journal of Chemical Ecology, 2020)
Cowpea, Vigna unguiculata L. Walp. (Fabaceae), is one of the most important food legumes grown on the African continent, as it provides an affordable source of dietary protein. Yields of cowpea are significantly reduced through damage by legume pod-borer, Maruca vitrata (Lepidoptera: Crambidae) , caterpillars to flowers, tender leaves and pods. Semiochemical-based strategies are considered as environmentally benign and affordable for pest management, particularly on smallholder farms. In this study, we investigated the importance of cowpea flower volatiles as host location cues for egg-laying M. vitrata , and herbivore-induced plant volatiles (HIPVs) as M. vitrata repellents and natural enemy ( Apanteles taragamae and Phanerotoma syleptae parasitoid) attractants. In oviposition choice assays, M. vitrata laid more eggs on flowering cowpea plants than non-flowering plants. Coupled gas chromatography-electrophysiology (GC-EAG) analysis using the antennae of female M. vitrata and an extract of flower volatiles collected by dynamic headspace collection revealed the presence of five EAG-active components that were identified by coupled GC-mass spectrometry (GC-MS) analysis as benzaldehyde, benzyl alcohol, acetophenone, a vinylbenzaldehyde isomer and ( E )-cinnamaldehyde. A synthetic blend of the identified compounds, prepared using 3-vinylbenzaldehyde, induced M. vitrata to lay as many eggs on non-flowering cowpea as on flowering plants. The moths also preferred laying eggs on intact plants compared to M. vitrata -infested plants. As the emission of EAG-active floral compounds was determined to be lower in the headspace of infested cowpea flowers, the role of HIPVs emitted by M. vitrata -damaged leaves was also investigated. Of the compounds induced by larval damage, ( E )-DMNT, indole, n-hexyl acetate, 1-octen-3-ol and linalool were shown by GC-EAG to possess electrophysiological activity. A synthetic blend of the EAG-active compounds, using racemic 1-octen-3-ol and linalool, significantly reduced egg numbers on flowering cowpea. Larval and egg parasitoids, i.e. A. taragamae and Ph. syleptae, respectively, of M. vitrata both preferred the Y-tube olfactometer arm treated with synthetic ( E )-DMNT, whereas preference for racemic linalool and ( E )-nerolidol was dose-dependent in A. taragamae . Our results provide the platform for the development of future semiochemical-based pest management strategies against M. vitrata on smallholder farms in West Africa.

The Application of Heavy Strength Training in Relative Energy Deficiency in Sport - David R. Hooper (Journal of Science in Sport and Exercise, 2019)

Ecosystem context illuminates conflicting roles of plant diversity in carbon storage - E. Carol Adair; David U. Hooper; Alain Paquette; Bruce A. Hungate (Ecology Letters, 2018)
Plant diversity can increase biomass production in plot‐scale studies, but applying these results to ecosystem carbon (C) storage at larger spatial and temporal scales remains problematic. Other ecosystem controls interact with diversity and plant production, and may influence soil pools differently from plant pools. We integrated diversity with the state‐factor framework, which identifies key controls, or ‘state factors’, over ecosystem properties and services such as C storage. We used this framework to assess the effects of diversity, plant traits and state factors (climate, topography, time) on live tree, standing dead, organic horizon and total C in Québec forests. Four patterns emerged: (1) while state factors were usually the most important model predictors, models with both state and biotic factors (mean plant traits and diversity) better predicted C pools; (2) mean plant traits were better predictors than diversity; (3) diversity increased live tree C but reduced organic horizon C; (4) different C pools responded to different traits and diversity metrics. These results suggest that, where ecosystem properties result from multiple processes, no simple relationship may exist with any one organismal factor. Integrating biodiversity into ecosystem ecology and assessing both traits and diversity improves our mechanistic understanding of biotic effects on ecosystems.

The presence of symptoms of testosterone deficiency in the exercise-hypogonadal male condition and the role of nutrition - David R. Hooper; William J. Kraemer; Catherine Saenz; Kevin E. Schill; Brian C. Focht; Jeff S. Volek; Carl M. Maresh (European Journal of Applied Physiology, 2017)

Effects of resource addition on recovery of production and plant functional composition in degraded semiarid grasslands - Qing Chen; David U. Hooper; Hui Li; Xiao Ying Gong; Fei Peng; Hong Wang; Klaus Dittert; Shan Lin (Oecologia, 2017)

Solidago gigantea plants from nonnative ranges compensate more in response to damage than plants from the native range - Huixuan Liao; Priscila C. S. Gurgel; Robert W. Pal; David Hooper; Ragan M. Callaway (Ecology, 2016)
Resistance and tolerance are two ways that plants cope with herbivory. Tolerance, the ability of a plant to regrow or reproduce after being consumed, has been studied less than resistance, but this trait varies widely among species and has considerable potential to affect the ecology of plant species. One particular aspect of tolerance, compensatory responses, can evolve rapidly in plant species; providing insight into interactions between consumers and plants. However, compensation by invasive species has rarely been explored. We compared compensatory responses to the effects of simulated herbivory expressed by plants from seven Solidago gigantea populations from the native North American range to that expressed by plants from nine populations from the nonnative European range. Populations were also collected along elevational gradients to compare ecotypic variation within and between ranges. Solidago plants from the nonnative range of Europe were more tolerant to herbivory than plants from the native range of North America. Furthermore, plants from European populations increased in total biomass and growth rate with elevation, but decreased in compensatory response. There were no relationships between elevation and growth or compensation for North American populations. Our results suggest that Solidago gigantea may have evolved to better compensate for herbivory damage in Europe, perhaps in response to a shift to greater proportion of attack from generalists. Our results also suggest a possible trade‐off between rapid growth and compensation to damage in European populations but not in North American populations.

Estimating local biodiversity change: a critique of papers claiming no net loss of local diversity - Andrew Gonzalez; Bradley J. Cardinale; Ginger R. H. Allington; Jarrett Byrnes; K. Arthur Endsley; Daniel G. Brown; David U. Hooper; Forest Isbell; Mary I. O'Connor; Michel Loreau (Ecology, 2016)
Global species extinction rates are orders of magnitude above the background rate documented in the fossil record. However, recent data syntheses have found mixed evidence for patterns of net species loss at local spatial scales. For example, two recent data meta‐analyses have found that species richness is decreasing in some locations and is increasing in others. When these trends are combined, these papers argued there has been no net change in species richness, and suggested this pattern is globally representative of biodiversity change at local scales. Here we reanalyze results of these data syntheses and outline why this conclusion is unfounded. First, we show the datasets collated for these syntheses are spatially biased and not representative of the spatial distribution of species richness or the distribution of many primary drivers of biodiversity change. This casts doubt that their results are representative of global patterns. Second, we argue that detecting the trend in local species richness is very difficult with short time series and can lead to biased estimates of change. Reanalyses of the data detected a signal of study duration on biodiversity change, indicating net biodiversity loss is most apparent in studies of longer duration. Third, estimates of species richness change can be biased if species gains during post‐disturbance recovery are included without also including species losses that occurred during the disturbance. Net species gains or losses should be assessed with respect to common baselines or reference communities. Ultimately, we need a globally coordinated effort to monitor biodiversity so that we can estimate and attribute human impacts as causes of biodiversity change. A combination of technologies will be needed to produce regularly updated global datasets of local biodiversity change to guide future policy. At this time the conclusion that there is no net change in local species richness is not the consensus state of knowledge.

Influence of training on markers of platelet activation in response to a bout of heavy resistance exercise - Brent C. Creighton; Brian R. Kupchak; Juan C. Aristizabal; Shawn D. Flanagan; Courtenay Dunn-Lewis; Brittanie M. Volk; Brett A. Comstock; Jeff S. Volek; David R. Hooper; Tunde K. Szivak; Carl M. Maresh; William J. Kraemer (European Journal of Applied Physiology, 2013)

Sex differences in creatine kinase after acute heavy resistance exercise on circulating granulocyte estradiol receptors - Megan R. Wolf; Maren S. Fragala; Jeff S. Volek; Craig R. Denegar; Jeffrey M. Anderson; Brett A. Comstock; Courtenay Dunn-Lewis; David R. Hooper; Tunde K. Szivak; Hui-Ying Luk; Carl M. Maresh; Keijo Häkkinen; et al. (European Journal of Applied Physiology, 2012)

Effects of altitude exposure on brain natriuretic peptide in humans - David Woods; Tim Hooper; Pete Hodkinson; Steve Ball; Rob Wakeford; Bob Peaston; Claire Bairsto; Nic Green; Adrian Mellor (European Journal of Applied Physiology, 2011)

Effects on kidney disease, fertility and development in mice inheriting a protein-truncating Denys-Drash syndrome allele (Wt1 tmT396) - Charles E. Patek; David G. Brownstein; Stewart Fleming; Caroline Wroe; Lorraine Rose; Anna Webb; Rachel L. Berry; Paul S. Devenney; Marion Walker; Oliver D. K. Maddocks; Nicola J. Lawrence; David J. Harrison; et al. (Transgenic Research, 2008)

Scaling environmental change through the community‐level: a trait‐based response‐and‐effect framework for plants - KATHARINE N. SUDING; SANDRA LAVOREL; F. S. CHAPIN; JOHANNES H. C. CORNELISSEN; SANDRA DÍAZ; ERIC GARNIER; DEBORAH GOLDBERG; DAVID U. HOOPER; STEPHEN T. JACKSON; MARIE‐LAURE NAVAS (Global Change Biology, 2008)
Predicting ecosystem responses to global change is a major challenge in ecology. A critical step in that challenge is to understand how changing environmental conditions influence processes across levels of ecological organization. While direct scaling from individual to ecosystem dynamics can lead to robust and mechanistic predictions, new approaches are needed to appropriately translate questions through the community level. Species invasion, loss, and turnover all necessitate this scaling through community processes, but predicting how such changes may influence ecosystem function is notoriously difficult. We suggest that community‐level dynamics can be incorporated into scaling predictions using a trait‐based response–effect framework that differentiates the community response to environmental change (predicted by response traits) and the effect of that change on ecosystem processes (predicted by effect traits). We develop a response‐and‐effect functional framework, concentrating on how the relationships among species' response, effect, and abundance can lead to general predictions concerning the magnitude and direction of the influence of environmental change on function. We then detail several key research directions needed to better scale the effects of environmental change through the community level. These include (1) effect and response trait characterization, (2) linkages between response‐and‐effect traits, (3) the importance of species interactions on trait expression, and (4) incorporation of feedbacks across multiple temporal scales. Increasing rates of extinction and invasion that are modifying communities worldwide make such a research agenda imperative.

Overyielding among plant functional groups in a long‐term experiment - David U. Hooper; Jeffrey S. Dukes (Ecology Letters, 2004)
A recent debate among ecologists has focused on mechanisms by which species diversity might affect net primary productivity. Communities with more species could use a greater variety of resource capture characteristics, leading to greater use of limiting resources (complementarity) and therefore greater productivity (overyielding). Recent experiments, however, have shown a variety of relationships between diversity and productivity. In an experiment on serpentine grassland communities spanning 8 years, we found that overyielding increased several years after plot establishment. Overyielding varied greatly depending on the functional characteristics of the species involved and the biotic and abiotic environment (particularly water availability). While functional differences among species led to strong complementarity and facilitation, these effects were not sufficient to cause significant transgressive overyielding or consistent increases in productivity with increased plant diversity. These results suggest that greater absolute production with greater diversity may be restricted to particular species combinations or environmental conditions.

Vegetation and climate controls on potential CO 2 , DOC and DON production in northern latitude soils - Jason C. Neff; David U. Hooper (Global Change Biology, 2002)
Climatic change may influence decomposition dynamics in arctic and boreal ecosystems, affecting both atmospheric CO 2 levels, and the flux of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) to aquatic systems. In this study, we investigated landscape‐scale controls on potential production of these compounds using a one‐year laboratory incubation at two temperatures (10° and 30 °C). We measured the release of CO 2 , DOC and DON from tundra soils collected from a variety of vegetation types and climatic regimes: tussock tundra at four sites along a latitudinal gradient from the interior to the north slope of Alaska, and soils from additional vegetation types at two of those sites (upland spruce at Fairbanks, and wet sedge and shrub tundra at Toolik Lake in northern Alaska). Vegetation type strongly influenced carbon fluxes. The highest CO 2 and DOC release at the high incubation temperature occurred in the soils of shrub tundra communities. Tussock tundra soils exhibited the next highest DOC fluxes followed by spruce and wet sedge tundra soils, respectively. Of the fluxes, CO 2 showed the greatest sensitivity to incubation temperatures and vegetation type, followed by DOC. DON fluxes were less variable. Total CO 2 and total DOC release were positively correlated, with DOC fluxes approximately 10% of total CO 2 fluxes. The ratio of CO 2 production to DOC release varied significantly across vegetation types with Tussock soils producing an average of four times as much CO 2 per unit DOC released compared to Spruce soils from the Fairbanks site. Sites in this study released 80–370 mg CO 2 ‐C g soil C −1 and 5–46 mg DOC g soil C −1 at high temperatures. The magnitude of these fluxes indicates that arctic carbon pools contain a large proportion of labile carbon that could be easily decomposed given optimal conditions. The size of this labile pool ranged between 9 and 41% of soil carbon on a g soil C basis, with most variation related to vegetation type rather than climate.

Corrected calculations for soil and ecosystem measurements of CO2 flux using the LI-COR 6200 portable photosynthesis system - David U. Hooper; Zoe G. Cardon; F. Chapin; Michelle Durant (Oecologia, 2002)

High-resolution structures of the oxidized and reduced states of cytochrome c554 from Nitrosomonas europaea - Tina M. Iverson; David M. Arciero; Alan B. Hooper; Douglas C. Rees (JBIC Journal of Biological Inorganic Chemistry, 2001)

Population Pharmacokinetic Modeling of Steady State Carbamazepine Clearance in Children, Adolescents, and Adults - David M. Reith; Wayne D. Hooper; John Parke; Bruce Charles (Journal of Pharmacokinetics and Pharmacodynamics, 2001)

Velocity specificity in early training of the knee extensors after anterior cruciate ligament reconstruction - Matthew C. Morrissey; David M. Hooper; Wendy I. Dreschler; Helen J. Hill; Thomas Bucknill (European Journal of Applied Physiology, 2000)

Reliability of leg muscle electromyography in vertical jumping - Peter C. Goodwin; Kobus Koorts; Richard Mack; Shunfu Mai; Matthew C. Morrissey; David M. Hooper (European Journal of Applied Physiology, 1999)

Cytochrome c peroxidase from Methylococcus capsulatus Bath - James A. Zahn; David M. Arciero; A. B. Hooper; Joel R. Coats; A. A. DiSpirito (Archives of Microbiology, 1997)

Enzymology of the oxidation of ammonia to nitrite by bacteria - Alan B. Hooper; Todd Vannelli; David J. Bergmann; David M. Arciero (Antonie van Leeuwenhoek, 1997)